Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/j.1600-079x.2012.01020.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and functional mapping of human ASMT, the last enzyme of the melatonin synthesis pathway

Abstract: Melatonin is a synchronizer of many physiological processes. Abnormal melatonin signaling is associated with human disorders related to sleep, metabolism, and neurodevelopment. Here, we present the X-ray crystal structure of human N-acetyl serotonin methyltransferase (ASMT), the last enzyme of the melatonin biosynthesis pathway. The polypeptide chain of ASMT consists of a C-terminal domain, which is typical of other SAM-dependent O-methyltransferases, and an N-terminal domain, which intertwines several helices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 38 publications
(57 reference statements)
4
59
0
Order By: Relevance
“…The involvement of the ASMT gene in relation to ASD etiology has been studied extensively (Toma et al 2007; Cai et al 2008; Melke et al 2008; Jonsson et al 2010; Wang et al 2013). An ASD-risk haplotype was reported that includes two SNPs located in the promoter region, rs4446909 and rs5989681, and a third SNP, rs6644635, located in the 5′-untranslated region (UTR) of the only known functional isoform of ASMT (Melke et al 2008; Botros et al 2012). Further statistical studies have failed to replicate the associations of these common variants in ASMT with ASD risk (Toma et al 2007; Wang et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of the ASMT gene in relation to ASD etiology has been studied extensively (Toma et al 2007; Cai et al 2008; Melke et al 2008; Jonsson et al 2010; Wang et al 2013). An ASD-risk haplotype was reported that includes two SNPs located in the promoter region, rs4446909 and rs5989681, and a third SNP, rs6644635, located in the 5′-untranslated region (UTR) of the only known functional isoform of ASMT (Melke et al 2008; Botros et al 2012). Further statistical studies have failed to replicate the associations of these common variants in ASMT with ASD risk (Toma et al 2007; Wang et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…ASMT is the limiting enzyme in the synthesis of melatonin [25]. ASTM gene is located in the pseudoautosomal region of the X chromosome [26], which is a candidate region for the development of mental illness [27]. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the crystal structures of each enzyme involved in this pathway have been identified except for ASMT. Recently, the crystal structure of human ASMT has been successfully determined by Botros et al [8] and they confirmed its presence in the human pineal gland. To further elucidate the impact of ASMT mutations on melatonin synthesis, the crystal structures of ASMT in complex with SAM and SAM + NAS were also deposited in the protein data bank.…”
mentioning
confidence: 81%
“…On the carboxylate group of E311 [8]. A proton of H255 is abstracted by the E311, which enhances the possibility of the proton transferring from the hydroxyl of NAS to H255.…”
Section: Model Fmentioning
confidence: 99%
See 1 more Smart Citation